Optimization of Spore Purification and Quality Assessment in Paenibacillus Species - Souichirou Kawai; Miyo Nakano (Journal of Food Protection)
To enhance the consistency and quality of Paenibacillus spore preparations used in food safety research, we examined two widely adopted purification methods—lysozyme treatment and HistDenz gradient centrifugation—under different sporulation conditions (solid agar and liquid media). Spores from four Paenibacillus strains (P. odorifer JCM 21743T and JCM 13339, P. terrae JCM 11466T, and P. polymyxa JCM 2507T) were purified and evaluated for metabolic activity using 5-cyano-2,3-ditolyl tetrazolium chloride (CTC) staining and for germination capacity through growth curve analysis. CTC staining verified the complete absence of metabolically active vegetative cells in all purified samples. Growth assays demonstrated that lysozyme treatment reduced spore viability in certain strains, whereas HistDenz purification more reliably preserved germination potential. Additionally, spores generated on solid medium displayed improved growth performance—evidenced by higher peak turbidity and shorter doubling times—compared to those produced in liquid medium for selected strains. These results demonstrate that both the purification technique and sporulation environment have a significant impact on the physiological quality of Paenibacillus spores. Therefore, selecting strain-specific preparation protocols is essential for accurately assessing spore viability and ensuring their effective application in downstream detection or safety assessments.